The Efforts of SKI (History of Islam Culture) Teacher's in Improving Interests and Achievement of Students in MAN Panyabungan Mandailing Natal Regency - Nuraini Nuraini (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to provide information and images for school principals and teachers. Especially teachers of Islamic Cultural History subjects about how teachers' efforts in increasing student interest and learning achievement as evaluation material to further improve the quality of education. Early research was conducted at MAN Panyabungan Mandailing Natal Regency for 4 teachers. The method used in this research is interview and observation, the results of interviews and observations are collected to be tested for validity by the data triangulation method. The results of the study found that to increase the interest and achievement of special students by the teacher in the subjects of Islamic history and culture is to pay attention to their interests and abilities, give gifts and praise when they succeed or understand the theme of the lesson, then give a penalty in the form of challenges that are not far away from the interests they have. So the prsetasi and interest in learning in students and students will be more explored again.